A methodological critique of Munshi's model on clientelism, public goods, and divided democracies - Cendales, Andrés; Guerrero, Hugo; Mora, Jhon James (Frontiers in Political Science, 2025)
As social scientists, we find Soumyanetra Munshi's theoretical work on the dilemma between clientelism and public goods in divided democracies both fascinating and thought-provoking. However, this article addresses two core issues in her model. The dialogue is guided by a perspective in formal modeling that emphasizes the analytical relevance of conclusions that may appear absurd, as well as internal contradictions. We critique Munshi's model by first discussing a paradoxical outcome, followed by a logical inconsistency.